The Use of Rituximab in Glomerulonephritis: What Is the Evidence? - Wenjuan Zhu; Haiyan He; Pearl Pai (Biomedicines, 2025)
Rituximab has been increasingly used as a choice of treatment in various forms of glomerulonephritis. Recent evidence and the KDIGO guideline establish Rituximab as the first-line treatment for Primary Membranous Nephropathy and ANCA-associated vasculitis. It is also recommended in cases of steroid-dependent or frequently relapsing Minimal Change Disease and Focal Segmental Glomerulosclerosis, as well as in refractory Lupus Nephritis. In this review, we set out to analyze the evidence behind its use and some of its shortfalls, including gaps in understanding the dosing and redosing schedule, as well as long-term safety, which advocate for further research. Finally, we also provide some practical tips on patient use.